2017
DOI: 10.1002/chem.201700638
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Bonding Properties of N‐Heterocyclic Carbenes (NHCs): A Systematic Charge‐Displacement Analysis

Abstract: In view of their intensive use as ligands in many reactions catalyzed by transition-metal complexes, modulation of the bonding properties of N-heterocyclic carbenes (NHCs) on a rational basis is highly desirable, which should enable optimization of current applications or even promote new functions. In this paper, we provide a quantitative analysis of the chemical bond between a metal fragment AuCl and a series of 29 different NHCs in [(NHC)AuCl] complexes. NHCs electronic properties are modified through: i) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 92 publications
6
55
0
Order By: Relevance
“…On the other hand, the Au-Se bond remains practically unchanged, probably for the compensation of different effects. The decrease of the Au → C back-donation may appear small but it should be considered that the donor/acceptor properties of the carbene are only slightly influenced by chemical modifications on the carbene structure [23,69,70], and, on the other side, activation barriers can be quite sensible to back-donation [71]. The same gold complexes, in the presence of a stronger and more structured XB donor as NIS, gave different results.…”
Section: Condensed Phasementioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, the Au-Se bond remains practically unchanged, probably for the compensation of different effects. The decrease of the Au → C back-donation may appear small but it should be considered that the donor/acceptor properties of the carbene are only slightly influenced by chemical modifications on the carbene structure [23,69,70], and, on the other side, activation barriers can be quite sensible to back-donation [71]. The same gold complexes, in the presence of a stronger and more structured XB donor as NIS, gave different results.…”
Section: Condensed Phasementioning
confidence: 98%
“…Above all, it provided to be extremely versatile in coordination chemistry. Indeed, thanks to the possibility of decomposing the charge rearrangement upon the bond formation between two species into contributions (see Methodological Aspects), it has been extensively used to characterize metal-ligand bonds [21][22][23][24][25] providing, in some cases, an elegant theoretical framework to better rationalize experimental results [26][27][28][29]. Very recently, CD analysis was the key tool for revealing unexpected acceptor properties of helium atoms [30,31].…”
mentioning
confidence: 99%
“…However, only a small subset of these NOCV pairs actually contributes to the overall charge rearrangement Δ ρ ’ because a large part of them presents eigenvalues close to zero . The CD‐NOCV approach has been successfully applied for the characterization of transition metal compounds and for disentangling donation and backdonation in the CD function of non‐symmetric systems containing NHC−Au(I) bond, Au(I)−H bond or Au(III)−CO bond with different ancillary ligands …”
Section: Methodsmentioning
confidence: 99%
“…However, only a small subset of these NOCV pairs actually contributes to the overall charge rearrangement Δ1' because a large part of them presents eigenvalues close to zero. [18] The CD-NOCV approach has been successfully applied for the characterization of transition metal compounds [19] and for disentangling donation and backdonation in the CD function of non-symmetric systems containing NHCÀ Au(I) bond, [20] Au(I)À H bond [21] or Au (III)À CO bond with different ancillary ligands. [22] Well-defined measurements of the total charge transfer (denoted as CT net ) and of its σ donation and perpendicular and parallel π backdonation contributions (denoted as CT σÀ d°n , CT πÀ back ⊥ and CT πÀ back k , respectively) are obtained by evaluating the corresponding CD-NOCV function at the "isodensity boundary".…”
Section: Cd-nocv Methodsmentioning
confidence: 99%
“…A charge displacement study of different [(NHC)AuCl] complexes showed that the NHC bonding properties are quite robust against variation of the structure. This study was extended with [(NHC)PPh] adducts and it was shown that the 31 P NMR chemical shift only qualitatively correlates with the π acceptor properties of the NHCs . A recent computational study of various [(NHC)AuCl] complexes focused on Au NMR found a correlation between the π‐accepting ability of these complexes and the 197 Au chemical shift .…”
Section: Introductionmentioning
confidence: 93%